Thai Early Childhood Education Quality Assurance Assessor Competency Development Analysis - Khanidtha Tangwarasittichai; Punnee Leekitchwatana; Paitoon Pimdee (My University, 2021)
In Thailand, starting in 2000, education quality assessment was tasked to the Office for National Education Standards and Quality Assessment (ONESQA).Subsequently, 5-year cycles (rounds) were established to assess Thai educational institutions.In Round 1, 35,134 schools at the basic education level were assessed.Subsequently, numerous issues concerning the external assessors' (EA) competency were raised.Therefore we undertook a 2nd-order confirmatory factor analysis (CFA) of the study's three latent and 17 observed variables concerning early childhood education EA competency.Multi-stage random sampling was used to conduct the sample survey of 400 early childhood education quality assurance (QA) EAs across 40 Thai provinces covering four regions.IBM's® SPSS® Amos™ 24 software was used for the analysis.Results revealed that EAs perceived their information technology skills (SH) as critical.This was followed by early childhood education knowledge (KA) and true friends (AA).
Keywords: Early Childhood Education and Development